Exploring the impact of hydrogen peroxide delivery methods on PaDa-I enzyme deactivation during styrene biotransformation within tandem catalysis framework - Mukwenya, Rufaro (Department of Chemical Engineering, 2025)
Biocatalysis has become an attractive method for hydrocarbon activation due to its alignment with the principles of green chemistry. Enzymes are advantageous over traditional metal-based catalysts because they are obtained from renewable sources, typically require mild reaction conditions, and are highly selective. A few classes of enzymes have been identified as active in these transformations including oxygenases, oxidases, hydroxylases, peroxidases and peroxygenases. One of the most promising classes of enzymes are unspecific peroxygenases (UPOs). These enzymes are able to use hydrogen peroxide (H2O2) as the oxidant and electron donor without the need for expensive co-factors. The main challenge is the deactivation of UPOs in reaction systems containing excess H2O2. A potential approach to circumvent this deactivation is to produce the hydrogen peroxide in-situ in a one-pot tandem catalytic system. However, this system is poorly understood with very little kinetic data reported in the literature. In this study, different hydrogen peroxide delivery methods and concentrations were investigated to minimise enzyme deactivation. The delivery methods were once-off addition where the hydrogen peroxide was added all at once, stepwise addition where it was added at regular intervals and continuous addition where it was fed gradually at a controlled rate using a syringe pump. In addition, the influence of reaction temperature and pH on the enzyme's stability were investigated. Thereafter, the obtained optimised process conditions were evaluated in a hydrocarbon biotransformation reaction, using styrene as the model substrate. The PaDa-I enzyme (UPO variant) lost approximately 90% of its initial activity during the early stages of the reaction. This was significantly higher than the 50% and 40% activity lost when the enzyme was exposed to hydrogen peroxide and styrene as sole substrates. Despite the significant activity loss, a turnover number of 3 070 molproduct molprotein -1 was achieved employing semi-continuous addition which was determined to be the best H2O2 delivery method. A full kinetic study investigating the deactivation of the PaDa-I enzyme was also performed. Three enzyme deactivation models were tested to model the experimental data by nonlinear regression, these kinetic models were first order, two-parameter and four-parameter models. It was established that the two-parameter model best fit the experimental data. This kinetic model described a deactivation pathway where the enzyme is not completely deactivated, but rather transformed to less reactive intermediates over time upon exposure to excess hydrogen peroxide. The crucial kinetic parameter obtained from this model was the ratio of the final (less active form) and initial specific enzyme activity α1. The α1 value of 0.07 obtained for the styrene biotransformation was approximately an order of magnitude lower compared to the studies using hydrogen peroxide and styrene as sole substrates. Further insights on the kinetics of this biotransformation revealed that hydrogen peroxide behaved as a non-competitive inhibitor. This suggested that hydrogen peroxide was bound to an allosteric site on the enzyme, which distorted the structure of the enzyme making it less effective for styrene oxidation. The H2O2 concentration or delivery rate should therefore be reduced to further minimise this inhibition. The findings in this study will form the basis for future tandem systems that combine in-situ H2O2 production with hydrocarbon biotransformation using UPOs.